Accessibility to prenatal care at the Street Outreach Office: nurse perceptions in northern Brazil - Nayara Gonçalves Barbosa; Karoline Cardoso Netto; Lise Maria Carvalho Mendes; Thaís de Oliveira Gozzo; Herla Maria Furtado Jorge; Andyara do Carmo Pinto Coelho Paiva; Thaís Vasconcelos Amorim; Flávia Azevedo Gomes-Sponholz (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to understand nurse perspectives regarding homeless pregnant women's accessibility to prenatal care. Methods: a qualitative study, with analysis based on the concept of accessibility. Semi-structured interviews were carried out with 11 nurses who work at the Street Outreach Office in northern Brazil. Results: nurses are faced with geographic barriers and dangerous situations in border regions, recognizing that there is a context of physical, sexual and psychological violence that involves homeless pregnant women who seek care at the Street Outreach Office. Street Outreach Office nurses' work occurs in conjunction with other services in the Health Care Network. The implementation of educational measures is a powerful strategy, as is establishing links with women. Final Considerations: the Street Outreach Office's work provides meetings with pregnant women on site in the territory, which can provide geographic and socio-organizational accessibility to prenatal care.